Implementasi Rencana Induk Percepatan Pembangunan Papua (RIPPP) dan Sistem Informasi Percepatan Pembangunan Papua (SIPPP): Tantangan dan Prospek Menuju Papua Mandiri, Adil, dan Sejahtera - Ahmad, Thifli; Jamil, Alfan; Zidan, Ahmad; Huda, Yusril (Universitas Pahlawan Tuanku Tambusai, 2024)
Vice President of Indonesia, Ma'ruf Amin, launched the Papua Development Acceleration Master Plan (RIPPP) and the Papua Development Acceleration Information System (SIPPP) in Sorong, Southwest Papua. Information System for Accelerating Papua Development (SIPPP) in Sorong, Southwest Papua, on June 7, 2024. RIPPP 2022-2041 is designed with a vision of “The realization of an Independent, Just and Prosperous” and three main missions: Healthy Papua, Smart Papua, and Productive Papua. Productive. Development policies and strategies are directed at strengthening the role of new autonomous regional governments, by strengthening regulations, integrated planning, and utilization of information technology through SIPPP. Although the RIPPP and SIPPP have a clear vision, implementation challenges on the ground, such as infrastructure limitations and the potential for budget misuse, must be addressed through close supervision, increased human resource capacity, budget transparency, and cooperation with the private sector and non-governmental organizations. Organizations.